Model Pemberdayaan Masyarakat Melalui Pola Magang Tradisional Dalam Upaya Peningkatan Wirausaha Masyarakat - Danial, Adang; Darusman, Yus; Mustakim, Mustakim; Herwina, Wiwin (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Problema lower literacy rates in Sub Cipawitra Mangkubumi District of Tasikmalaya impact on unemployment. Unemployment is a problem that requires a special close attention. The unemployment rate in over productive (aged 15 years and above) will have an impact on the increasing number of criminal, immoral, and illegal. The purpose of community service is the creation of a model of community empowerment in the field of sewing business, increased knowledge, skills and attitudes in entrepreneurship. In collaboration with community service Courses and Training Institute (CGC) Anugrah Pratama and Forums Community Activity Center (CLC) Tasikmalaya. Method of implementation of community service uses two stages, among others: the preparation phase and implementation phase. During the implementation phase includes four stages include: identification of skills learned, the implementation phase, the assessment phase, and the follow-up phase. The results of community service activities can create new entrepreneurs in the sewing business.